Thyroid disorders in the first trimester of pregnancy: a cross-sectional study - Shankarappa, Rashmi; Parvathreddy, Spoorthy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Thyroid disorders in pregnancy are common and are associated with adverse maternal, fetal and neonatal effects. When the prevalence of thyroid disorders is high, then screening for thyroid disorders in early pregnancy can help improve the obstetrical outcome. Methods: Five hundred and fifty women in their first trimester of pregnancy were studied. They were investigated for estimation of free triiodo thyronine (FT3), free thyroxine (FT4) and thyroid stimulation hormone (TSH). The upper normal limit for TSH considered was 4.0 mIU/L. Results: Prevalence of thyroid disorders in the study was 12.6%. Hypothyroidism (12%) was more common than hyperthyroidism (0.6%). Subclinical hypothyroidism was present in 10%. Conclusions: Screening of thyroid disorders is to be considered for all pregnant women. As the prevalence of thyroid disorders is high, early recognition and treatment shall reduce maternal and fetal morbidity.